Variação dos Fluxos de Co2 e da Radiação Fotossinteticamente Ativa (par) em Ecossistema de Manguezal Amazônico na Região de Bragança, PA* - de Andrade, Vanda Maria Sales; Silva, Marcos Antonio Vanderlei; da Costa, José Maria Nogueira; Oliveira, Evandro C.; Malhi, Yadvinder (Ciência e Natura, 2007)
The objectives of this work were to quantify the magnitudesof the fluxes of CO2, and PAR at a mangrove ecosystem, and to analyzethe diurnal and seasonal variations. The fluxes of CO2, showed diurnal andseasonal variations very well characterized. The mean values of CO2, duringthe whole period were – 11.51 μmol.m-2.s-1.